Evaluating the multi-faceted effect of concurrent front-of-pack nutrition and ecolabels on food evaluation - Rramani Dervishi, Qëndresa; Dohle, Simone (Food quality and preference, 2025)
Front-of-pack labels (FOPLs) are a common strategy employed to promote healthy and sustainable food choices. In the recent years, there has been an increased tendency to highlight not only healthiness but also sustainability aspects via different FOPLs, thereby resulting in multiple labelling. Although relevant, the effects of concurrent FOPLs on food evaluation are yet unclear. To shed light on this question, we conducted two representative studies online (N = 996 and N = 1080) where we asked participants to rate 15 branded (Study 1) and 15 generic (Study 2) snack foods presented with corresponding nutrition and ecolabels in terms of perceived healthiness, sustainability, liking, wanting, and willingness to purchase. Both studies employed a 2 × 2 between-subject design with two factors: Nutri-Score (positive, negative) and Eco-Score (positive, negative). Results indicated that both branded and generic foods received higher healthiness and sustainability ratings when presented with positive Nutri- and Eco-Scores, respectively. Interestingly, Nutri-Score affected sustainability ratings as well, supporting that its effects may generalize to other ratings. Branded food items with two negative labels were liked significantly more than branded food items with two positive labels (Study 1), however these effects were not replicated when using generic food items (Study 2). These findings suggest that while label effects on healthiness and sustainability appear consistent, their effects on liking, wanting, and willingness to purchase are limited and likely modulated by other factors. Future research should investigate how label-induced shifts in food evaluations translate to food choices in the presence of multiple labels. •Two online studies assessed the effect of concurrent labels on food evaluations.•Concurrent Nutri- and Eco-Scores exert multifaceted effects on food evaluations.•Nutri- and Eco-Score robustly impact sustainability and healthiness ratings.•Nutri-Score affects perceived sustainability too, indicating a broader influence.•Neither label consistently affects liking, wanting, nor willingness to purchase.